2020
DOI: 10.1371/journal.pone.0241776
|View full text |Cite
|
Sign up to set email alerts
|

Colonisation with extended spectrum beta-lactamase-producing and carbapenem-resistant Enterobacterales in children admitted to a paediatric referral hospital in South Africa

Abstract: Introduction There are few studies describing colonisation with extended spectrum beta-lactamase-producing Enterobacterales (ESBL-PE) and carbapenem-resistant Enterobacterales (CRE) among children in sub-Saharan Africa. Colonisation often precedes infection and multi-drug-resistant Enterobacterales are important causes of invasive infection. Methods In this prospective cross-sectional study, conducted between April and June 2017, 200 children in a tertiary academic hospital were screened by rectal swab for E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
1
9
1
Order By: Relevance
“…In contrast to the low prevalence of MRSA colonization, the current study observed that almost two-thirds of children were colonized with potential ESBL-PE with a predominance of E. coli and K. pneumoniae complex. Similar findings regarding the colonization of ESBL producing E. coli and K. pneumoniae complex were reported in the same region among admitted neonates and street children [ 8 , 22 ], as well as other settings in LMIC [ 23 , 24 , 25 , 26 , 27 ] among non-HIV infected children. However, the prevalence was twice as high as that reported in HIC among non-HIV infected children [ 28 ], which could be attributed to poor hygiene, infrastructure and water sanitation, as documented previously in a meta-analysis [ 29 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast to the low prevalence of MRSA colonization, the current study observed that almost two-thirds of children were colonized with potential ESBL-PE with a predominance of E. coli and K. pneumoniae complex. Similar findings regarding the colonization of ESBL producing E. coli and K. pneumoniae complex were reported in the same region among admitted neonates and street children [ 8 , 22 ], as well as other settings in LMIC [ 23 , 24 , 25 , 26 , 27 ] among non-HIV infected children. However, the prevalence was twice as high as that reported in HIC among non-HIV infected children [ 28 ], which could be attributed to poor hygiene, infrastructure and water sanitation, as documented previously in a meta-analysis [ 29 ].…”
Section: Discussionsupporting
confidence: 83%
“…A total of 399 children below five years of age were enrolled with a median [interquartile range [IQR] age of 19 [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] months and 212 (53%) were males. The gender distribution was almost equal between two groups ( p = 0.463).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the detection of ESBL enzymes at DRH (55.8%), which is located in the northern part of Ethiopia, was comparatively low. However, the lower level of ESBL detection at DRH was still higher compared to studies conducted in South Africa [31], Mozambique [20] and South and South East Asia [32]. While it is known that the spread of ESBL genes varies geographically [33], the factors that contribute to its high occurrence in some hospitals and a lower detection rate in the other hospital within a single country requires investigation so that effective control mechanisms can be designed.…”
Section: Discussionmentioning
confidence: 88%
“…The emergence of colistin- and carbapenem-resistant K. pneumoniae is a major concern owing to limited treatment options. Epidemiological data in South Africa shows an increased prevalence of carbapenemase-positive Gram-negative bacteria and a low prevalence of mcr genes within the public health sector 4,14,25,26 . However, there are carbapenem- and colistin-resistant isolates without any known resistance mechanism.…”
Section: Discussionmentioning
confidence: 99%